"Got rats?" Global environmental costs of thirst for milk include acute biodiversity impacts linked to dairy feed production. (4th May 2018) - Luque‐Larena, Juan J.; Mougeot, François; Arroyo, Beatriz; Lambin, Xavier
Abstract : Rodents damaging alfalfa crops typically destined for export to booming Eastern markets often cause economical losses to farmers, but management interventions attempting to control rodents (i.e., use of rodenticides) are themselves damaging to biodiversity. These damages resonate beyond dairy feed producing regions through animal migration and are an overlooked part of the transferred environmental burden caused by a growing thirst for milk in China and elsewhere.